2005
DOI: 10.1111/j.1532-5415.2005.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Race and Sex Differences in Age‐Related Hearing Loss: The Health, Aging and Body Composition Study

Abstract: Hearing loss was extremely common in this population. Because many of the identified hearing loss risk factors are modifiable, some of the burden associated with hearing loss in older people should be preventable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
247
6
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 286 publications
(290 citation statements)
references
References 42 publications
23
247
6
1
Order By: Relevance
“…[2] According to a study by Helzner, et al it is found to be more common in men than women. [11] In our study also we found majority of patients of older age groups above 65 years.…”
Section: Discussionsupporting
confidence: 59%
“…[2] According to a study by Helzner, et al it is found to be more common in men than women. [11] In our study also we found majority of patients of older age groups above 65 years.…”
Section: Discussionsupporting
confidence: 59%
“…The reason attributed to this phenomenon in an earlier study was due to a higher prevalence of otitis media with effusion and retracted tympanic membranes in the Caucasian group compared to the African group [10]. Furthermore, a study in adults [31] indicated that Caucasians were also more likely to have hearing loss followed by non-Caucasian, black individuals.…”
Section: Discussionmentioning
confidence: 98%
“…Previous reports from large epidemiological studies (Cooper 1994;Helzner et al 2005;Agrawal et al 2008;Lin et al 2011a, b) and from smaller case-control studies of workers with occupational noise exposure (Jerger et al 1986;Ishii and Talbott 1998) have consistently demonstrated better hearing thresholds in black compared with white participants. A number of explanatory factors may be theoretically implicated to explain the observed association between race and hearing loss in these studies.…”
Section: Potential Mechanistic Pathwaysmentioning
confidence: 99%
“…Epidemiologic studies of large population-based cohorts have consistently demonstrated lower rates of hearing loss among black than white participants with the odds of hearing loss generally 40-60% lower in black individuals (Cooper 1994;Helzner et al 2005;Lin et al 2011b). These findings have also been corroborated in smaller epidemiological studies that have investigated rates of hearing loss in workers exposed to similar levels of occupational noise.…”
Section: Introductionmentioning
confidence: 99%